Innovative integration: optimizing performance through warm-up and photobiomodulation in high-intensity test - Santos, Izabela A.; Lemos, Marina Paiva; Puggina, Enrico Fuini; Mota, Gustavo R. (Frontiers in Sports and Active Living, 2024)
We investigated whether the application of photobiomodulation therapy (PBMT) immediately after a standardized warm-up (WU + PBMT) or traditional PBMT (no pre-warming) would influence performance in intermittent testing and intensity variables. In a counterbalanced randomized crossover design, twelve female futsal players (mean age: 23.9 ± 3.8 years) attended four sessions. Each session involved either a standardized warm-up or maintaining seated rest for five minutes. Subsequently, PBMT or placebo (with the PBMT device turned off) was applied, followed by the YoYo Intermittent Recovery Level 1 test (YYIR1) during which we assessed heart rate, rating of perceived exertion, and blood lactate levels. The performance in YYIIR1 was superior (p = 0.02) in the WU + PBMT condition (440.0 ± 59.0 m) compared to the WU + Placebo (353.3 ± 94.7 m), and placebo alone (no warm-up) (325.0 ± 67.2 m). We conclude that a combination of a specific warm-up before PBMT application improves high-intensity intermittent performance in amateur female futsal players without affecting intensity variables.